2020
DOI: 10.2196/19189
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multi-Parametric Magnetic Resonance Imaging in Standard of Care for Nonalcoholic Fatty Liver Disease: Protocol for a Randomized Control Trial

Abstract: Background The rising prevalence of nonalcoholic fatty liver disease (NAFLD) and the more aggressive subtype, nonalcoholic steatohepatitis (NASH), is a global public health concern. Left untreated, NAFLD/NASH can lead to cirrhosis, liver failure, and death. The current standard for diagnosing and staging liver disease is a liver biopsy, which is costly, invasive, and carries risk for the patient. Therefore, there is a growing need for a reliable, feasible, and cost-effective, noninvasive diagnostic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The diagnostic performance of cT1 for separating NAFLD from NASH in this study showed good sensitivity and specificity at a cT1 cut-off value of 800ms. This result further justifies the use of a previously defined cut-off value of cT1 ≥ 800ms, below which no further diagnostic evaluation is warranted [39,40] . The healthy participants from the UK biobank imaging study had a cT1 range of between 619-755ms suggesting that 800ms can be considered as the upper limit of normal for cT1.…”
Section: Meta-analysis Of Individual Clinical Studies Combinedmentioning
confidence: 65%
See 1 more Smart Citation
“…The diagnostic performance of cT1 for separating NAFLD from NASH in this study showed good sensitivity and specificity at a cT1 cut-off value of 800ms. This result further justifies the use of a previously defined cut-off value of cT1 ≥ 800ms, below which no further diagnostic evaluation is warranted [39,40] . The healthy participants from the UK biobank imaging study had a cT1 range of between 619-755ms suggesting that 800ms can be considered as the upper limit of normal for cT1.…”
Section: Meta-analysis Of Individual Clinical Studies Combinedmentioning
confidence: 65%
“…Biomarker performance for discriminating those with NASH from simple NAFLD was assessed using a cutoff of cT1≥800ms, MRI liver fat ≥5% or a combination of both. These cut-off values have been described previously as indicators for recommending further diagnostic evaluation [39,40] . Using the cut-off of cT1≥800ms to discriminate those with NASH resulted in a sensitivity of 75%, specificity of 66% and PPV and NPV both of 71%.…”
Section: Figure 1: [A] Boxplot Comparison Of Ct1 In Controls and Pati...mentioning
confidence: 99%
“…The potential of the proposed 2in1‐RARE‐EPI hybrid is not limited to MS lesions or even brain imaging. 2in1‐RARE‐EPI offers the capacity for simultaneous T 2 and T2 mapping in applications dealing with bulk or physiological motion, such as cardiac imaging including myocardial T 2 and T2 mapping, 102‐104 as well as multi‐parametric MRI of the eye, kidney, abdomen, and liver 105‐110 . For these applications in moving organs, motion correction approaches such as 1D or 2D linear phase correction promise to ensure immunity to bulk motion 111,112 .…”
Section: Discussionmentioning
confidence: 99%
“…2in1-RARE-EPI offers the capacity for simultaneous T 2 and T * 2 mapping in applications dealing with bulk or physiological motion, such as cardiac imaging including myocardial T 2 and T * 2 mapping, [102][103][104] as well as multi-parametric MRI of the eye, kidney, abdomen, and liver. [105][106][107][108][109][110] For these applications in moving organs, motion correction approaches such as 1D or 2D linear phase correction promise to ensure immunity to bulk motion. 111,112 The use of radial k-space trajectories shown in the current study holds the promise to render additional navigator data unnecessary because the densely sampled k-space center can be deployed for phase correction of motion corrupted data.…”
Section: And T *mentioning
confidence: 99%
“…[20][21][22][23] While no MCID was prespecified, prior studies support a relative reduction in hepatic fat of 30% or greater as clinically meaningful because that degree of change was associated with histological improvements in steatohepatitis [20][21][22][23] and fibrosis. 26 Prespecified nonkey secondary end points consisted of 6-month absolute changes in alanine aminotransferase (ALT), aspartate aminotransferase (AST), iron-corrected T 1 score, a validated composite MRI estimate of hepatic inflammation and fibrosis, 18,[27][28][29] VCTE-estimated liver fibrosis, body weight, and body mass index (calculated as weight in kilograms divided by height in meters squared). No MCID was prespecified for nonkey secondary outcomes.…”
Section: Primary Outcomementioning
confidence: 99%